2010
DOI: 10.1071/mf09222
|View full text |Cite
|
Sign up to set email alerts
|

Using DNA barcodes to connect adults and early life stages of marine fishes from the Yucatan Peninsula, Mexico: potential in fisheries management

Abstract: Barcoding has proven a useful tool in the rapid identification of all life stages of fish species. Such information is of critical importance for fisheries management and conservation, especially in high-diversity regions, such as Mexico’s marine waters, where more than 2200 species occur. The present study reports the barcode analysis of 1392 specimens from the Yucatan Peninsula, corresponding to 610 adults and juveniles, 757 larvae and 25 eggs, representing 181 species (179 teleosts and 2 rays), 136 genera a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
79
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 37 publications
3
79
0
1
Order By: Relevance
“…The limited number of characters, the multiple developmental stages, and the small size of immatures complicate taxonomic assignments (Busby et al 2000;Baldwin andSmith 2003, Richards 2006), making it unlikely that any comprehensive morphological identification system will be developed (Leis and Hay 2004). Molecular methods have gained increasing recognition as an alternative tool for species identification (Garland and Zimmer 2002), and several studies (e.g., Hubert et al 2010;Ko et al 2013;Valdez-Moreno et al 2010) have confirmed that one of these approaches, DNA barcoding, is a powerful tool for identifying larval fishes.…”
Section: Introductionmentioning
confidence: 99%
“…The limited number of characters, the multiple developmental stages, and the small size of immatures complicate taxonomic assignments (Busby et al 2000;Baldwin andSmith 2003, Richards 2006), making it unlikely that any comprehensive morphological identification system will be developed (Leis and Hay 2004). Molecular methods have gained increasing recognition as an alternative tool for species identification (Garland and Zimmer 2002), and several studies (e.g., Hubert et al 2010;Ko et al 2013;Valdez-Moreno et al 2010) have confirmed that one of these approaches, DNA barcoding, is a powerful tool for identifying larval fishes.…”
Section: Introductionmentioning
confidence: 99%
“…Second, overlaps in morphological stages and similarities among the eggs of related and unrelated cryptic taxa can lead to incorrect identifications (Hyde et al, 2005;Berrien and Sibunka 2 ;Gleason and Burton, 2012). Third, egg fixation in preservatives causes the loss of natural pigmentation and can obscure the developmental stage of an embryo (Valdez-Moreno et al, 2010). Finally, fixation can cause substantial egg shrinkage, a phenomenon that varies with preservative type and length of exposure (Hiemstra, 1962).…”
mentioning
confidence: 99%
“…Concerns over the use of a single locus to discriminate between closely allied species have been stressed since the DNA barcoding movement began; however, multiple studies have concluded that COI analysis is sufficient for species-level diagnoses. For example, this approach has been used successfully to barcode many Australian fish species (Ward et al, 2005) and to reveal overlooked marine species in the Indian Ocean (Zemlak et al, 2009). The method of DNA barcoding has also been used to connect the egg and larval stages of marine species along the coastline of Yucatan, Mexico, to their adult counterparts (Valdez-Moreno et al, 2010) and for a large-scale larval fish study in the Straits of Florida (Richardson et al, 2007;Richardson et al, 2010b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of early life stages, such as larvae and transforming young, is essential for current studies on the distribution and reproductive strategies of pelagic fishes (Takeyama et al 2001, Moura et al 2008, Valdez-Moreno et al 2010. Thus, the assessment of biodiversity and its implication in the management of vulnerable marine ecosystems requires an accurate taxonomic assignment of fish larvae.…”
Section: Introductionmentioning
confidence: 99%